Revisiting Delinquent Attitudes: Measurement, Dimensionality and Behavioral Effects - Thomas, Kyle J. (Journal of quantitative criminology, 2018)
This study examines whether single-item attitude measures commonly used in research adequately capture adolescent attitudes towards specific delinquent behaviors. It also explores whether delinquent attitudes form a unidimensional or multidimensional construct. Finally, this study tests Ajzen and Fishbein's principle of compatibility to determine if delinquent attitudes have a behavior-specific and a situation-specific effect on behavior.